The socio-demographic profile of the acceptor of copper intrauterine device after medical termination of pregnancy in a tertiary care centre - Shyam, Paresh; Ronghangpi, Mili; Rongphar, Ram Chandra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: India is going to be highest populous country within less than a decade. To stabilize population growth as well as to reduce maternal mortality and morbidity resulting from unwanted pregnancy, greater utilization of the spacing methods is essential. In spite of several decades of effort the popularity of Cu-T among the Indian woman is not high. Aim of the study was to find out the profile of the Cu-T acceptor after medical termination of pregnancy (MTP). Methods: It was a retrospective study. Socio-demographic data of the woman accepting Cu-IUCD after MTP was collected from family planning operation theatre record book. Results: The majority of the participants were from rural area. The mean age of the acceptor was 27.28±4.78. The maximum number of woman was para two 74 (44.3%). The number of woman with LCB 2 years or less than 2 years was 96 (57.5%) and that of woman with LCB more than two years was 71 (42.5%). Conclusions: A significant number of woman use Cu-T after a long gap of two years after last child birth. Woman found to be inclined to use Cu-T after having at least one male child.